Respuestas

  • Usuario de Brainly
2014-03-04T02:41:30+01:00
4√8-3√72 +4√50-3√18 = 4√4*2-3√4*18+4√2*25 -3√18 =
4*2√2 -3*2√18+4*5√2-3√18 = 8√2 -6√18 +20√2 -3√18 =28√2 -9√18

2/3√50+ 7/4√44 -5/6√245 - 3/2√396 = 2/3√25*2 +7/4√4*11 -5/6√49*5 -3/2√36*11 =
2/3*5√2 + 7/4*2√11 -5/6 *7√5 -3/2*6√11 =(10/3)√2 +(14/4)√11 -(35/6)√5-18/2√11
(10/3)√2 +(35/6)√5 +(7/2)√11-9√11
(10/3)√2 +(35/6)√5 +(7/2 -9 )√11
(10/3)√2 +(35/6)√5 +[ (7-18)/2]√11
10/3)√2 +(35/6)√5 -(11/2)√11

-(√3/8)- (π/√3) +(√3/4) -(2π/√3) = -√3/8 - π/√3 +√3/4 -2π/√3
-√3/8 +√3/4 -(π/√3+2π/√3) =(√3 +2√3)/8 -(3π/√3) =(3√3)/8 -(3π)/√3
 
     4√5 -5√2
     3√2 -2√5
----------------------
12√10 -15(√2)²
                       -8(√5)² +10√10
--------------------------------------------------
12√10 -15*2   -8*5 +10√10

22√10 -30 -40 = 22√10-70

(3am√4b²c^4)³ = (3am*2bc²)³ = 3³a³m³*2³b³c^6 = 27a³m³*8b³c^6
216a³m³b³c^6

√[(√7/10 + 7/√7) *√700/11] +7√7
√[[(√7)² +70)]/10√7 * √(7*100)/11] +7√7
√[(7+70)/10√7]*10√7 +7√7
√[(77/10√7) * 10√7/11] +7√7
√77/11 +7√7
√7*11/11+7√7
√7+7√7 =8√7